The current status of computers in education in public secondary schools in the state of Kedah Darul Aman - Abdul Karim, Abdul Malek (Universiti Utara Malaysia, 1995)
Today, nobody really needs convincing that the computer is an innovation of more than ordinary magnitude. The rapid advances in computer technology and the subsequent widespread utilization of computers, especially in the developed countries, have had dramatic impact on all aspects of society including education. The ever decreasing cost of computers and software has led to their increasing availability and application in schools. Developing countries in Asia are in the midst of introducing computers into education. In Malaysia, for example, computers were already present in a number of urban secondary schools in the early 1980s. More than ten years have passed since its introduction. Perhaps it is now time to look at the progress of the introduction of computers into education. This study, therefore, seeks to obtain and report information on the status of computers in education in public secondary schools in the state of Kedah Darul Aman. Specifically, it seeks to ascertain the extent of availability of computers/ computer facilities and the current and intended uses of computers. The study found that most (98.8%)of the schools surveyed have at least one computer. The total number of computers available is 649. However, the distribution is not equal as more than half of the schools have fewer than five computers. Due to the limited number of computers, many schools could not utilize their computers for computer education programmes. Instead, most schools utilize their computers for administrative purposes.